ИНГЛИЗ ТИЛИ ДАРСЛАРИДА МУТАХАССИСЛИККА ОИД МАТЕРИАЛЛАРДАН ФОЙДАЛАНИШ ТАЖРИБАСИДАН - Тажиева, А.У.; Бекмуратова, Н.А. (SCIENCE and SOCIETY, 2020)
The article deals with the issues of using the technology of content-based learning at English classes of higher educational establishments, ways of using professional texts as tools of learning. The author depicts the ways of developing geography students’ knowledge and skills by using “CLIL” (Content and Language Integrated Learning) approach.